Influence of Mild-Ozone Assisted Disperser Pretreatment on the Enhanced Biogas Generation and Biodegradability of Green Marine Macroalgae - Tamilarasan, Karuppiah; Banu, J. Rajesh; Kumar, M. Dinesh; Sakthinathan, G.; Park, Jeong-Hoon (Frontiers in Energy Research, 2019)
This study illustrated the participation of marine macroalgaebiomass (MAB) (Chaetomorpha antennina) in the liquefaction process for bioenergy production. The proposed work intended to investigate the role of disperser pretreatment (DP) and ozone disperser pretreatment (ODP) of MAB for energy efficient biogas generation. The disperser G-force of 1613 g, pretreatment time 30 min and ozone dosage 0.00049 g O3/g TS waspreferred as an optimum conditions for profitable and energy efficient liquefaction. On comparing DP and ODP, the MAB liquefaction and methane production potential was much higher (20.5 %, 0.20 g COD/g COD) in ODP when compared to DP (11.9 %, 0.11 g COD/g COD). Therefore, the ODP essentially improve the anaerobic biodegradability of MAB. The economic assessment showed that the ODP was found to have a higher net profit of 71 USD/ton of MAB compared to DP (4 USD/ton of MAB).